The Effect of Counter Pressure and Birthball on The Time of The First Stage of Labor and Prevention of Perineal Rupture - Anwar, Khalidatul Khair; Yustiari, Yustiari; Hasmia Naningsi; Asi, Melania (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Mothers with prolonged labor have a higher risk of bleeding. This study aimed to determine the effect of the counterpressure technique with a birthball on the length of the first stage of perineal rupture. This type of research is quantitative with a quasi-experimental design using an observation form conducted  in Kendari City Hospital from May to August 2023. The design used was a two-group-only post-test, with a control group. The study population comprised multiparous mothers in the first active stage. The sample size consisting of 20 who were given the counterpressure technique with birthball, 20 who were only given the counterpressure technique, and 20 who received no treatment. The inclusion criteria were mothers who were willing to become respondents and mothers who gave birth with normal births. The samples were collected using purposive sampling. The t-test was used to determine the differences between the three groups. The results of the difference test in the length of active phase I between the group given the counterpressure technique with birthball (intervention I) and the control group were p-value (0.000). The results of the analysis for the group given the counterpressure technique (Intervention II) with the control group were p-value (0.000). The results of the analysis for the group given the counterpressure technique with birthball (Intervention I) with the counterpressure technique (Intervention II) were p-value (0.759). In Conclusions, Providing counterpressure techniques with a birthball or simply providing counterpressure techniques is effective in reducing the incidence of perineal ruptures.